EXAMINING ISLAMIC EDUCATIONAL PHILOSOPHY AS A SPECIAL PHILOSOPHY - Darmanto; Asy'arie, Bima Fandi; Selly Susanti, Septiani; Fatimah, Siti; Muhammad, Adamu Abubakar (STIT Al - Ibrohimy Bangkalan, 2025)
Philosophy is a human endeavor that studies the essence through human reason by using reason to understand and answer all questions related to transcendence, humanism, and the human world. The object of philosophical study is inseparable from ontology, epistemology, and axiology. Data collection through “Google Scholar” and “ScienceDirect”, such as books, scientific articles, and proceedings, which are the main topic of discussion of the research topic. The discussion of this study’s object of general philosophy includes the history of the emergence of philosophy, characteristics of philosophical thinking, and the benefits of studying philosophy. As for the special branches of philosophy include “philosophy of education, history, science, law, social science, logic, art, religion, morals, and sports.” Then, on the object related to special philosophy, namely, the philosophy of educational practice and Islamic educational science. Studying philosophy can help understand the nature of truth, because it is necessary to study philosophy in the world of education. The study of philosophy can help assess the formulation of educational policies, understand the perception of differences in society, and change life by thinking critically.